CMIP5 Intermodel Relationships in the Baseline Southern Ocean Climate System and With Future Projections - Kajtar, JB; Santoso, A; Collins, M; Taschetto, AS; England, MH; Frankcombe, LM (Earth's Future, 2021)
This is the final version. Available on open access from Wiley via the DOI in this record Climate models exhibit a broad range in the simulated properties of the climate system. In the early historical period, the absolute global mean surface air temperature in Coupled Model Intercomparison Project, phase 5 (CMIP5) models spans a range of ~12-15 °C. Other climate variables may be linked to global mean temperature, and so accurate representation of the baseline climate state is crucial for meaningful future climate projections. In CMIP5 baseline climate states, statistically significant intermodel correlations between Southern Ocean surface temperature, outgoing shortwave radiation, cloudiness, the position of the mid-latitude eddy-driven jet, and Antarctic sea ice area are found. The baseline temperature relationships extend to projected future changes in the same set of variables. The tendency for models with initially cooler Southern Ocean to exhibit more global warming, and vice versa for initially warmer models, is linked to baseline Southern Ocean climate system biases. Some of these intermodel correlations arise due to a ‘capacity for change’. For example, models with more sea ice initially have greater capacity to lose sea ice as the planet warms, whereas models with little sea ice initially are constrained in the amount they can lose. Similar constraints apply to Southern Ocean clouds, which are projected to reduce under radiative forcing, and the jet latitude, which is projected to migrate poleward. A first look at emerging data from CMIP6 reveals a shift of the relationship from the Southern Ocean towards the Antarctic region, possibly due to reductions in Southern Ocean biases, such westerly wind representation. Natural Environment Research Council (NERC) Centre for Southern Hemisphere Oceans Research Australian Government National Environmental Science Program Australian Research Council (ARC)